Routes to diagnosis and missed opportunities in the detection of renal cancer. Issue 2 (February 2021) - Bradley, A.J.; Maskell, G.F.; Mannava, A.; Pollard, A.; Welsh, T.
Abstract : AIM: To determine the proportion of renal cancers for which incidental detection was the route to diagnosis, the characteristics of tumours identified in this way, and the frequency with which opportunities to make this diagnosis were missed. MATERIALS AND METHODS: Consecutive patients with renal cancers treated at Royal Cornwall Hospitals NHS Trust (April 2011 and July 2018 inclusive) were identified from the Trust's cancer registry database, and a retrospective review of the imaging and electronic case notes was undertaken. Mann–Whitney U -tests for comparison of patient age and tumour size at diagnosis, and chi-squared tests for comparing cell type distribution and grade were performed. Logistic regression was then used to identify the characteristics of patients in whom a renal tumour was missed initially. RESULTS: Of 327 patients, 194 (63%) presented incidentally, and 133 (37%) symptomatically. Incidentally detected cancers were found in younger patients, (median of 65 years versus 69 p= 0.01) and were smaller at presentation (median of 5.5 versus 7.2 cm, p< 0.00001). Thirty-six different reporters missed opportunities to diagnose renal cancer in 50 (16%) patients on 78 occasions, 28 lesions (35%) being missed more than once. Thirty were imaged incompletely; four were visible only on a single image and three on a scout view at magnetic resonance imaging. CONCLUSION: The commonest route to diagnosis of renal cancer is by incidental detection of a mass. In 16% of patients in whom renal cancer is diagnosed, there is at least one prior examination on which the lesion is visible at an earlier date. The clinical impact of these missed diagnostic opportunities remains uncertain. Highlights: Of 327 patients with renal cancer, 194 (63%) were detected as incidental findings. In 50 (16%), an opportunity to make the diagnosis on earlier imaging was missed. The clinical impact of these missed diagnostic opportunities remains uncertain. Lesion detection in retrospect does not imply that it should have been reported.